CHANGES IN THE ECOLOGICAL STATE OF LANDSCAPES AND THEIR ASSESSMENT: (ON THE EXAMPLE OF THE LARGE CITIES OF THE FERGANA VALLEY) (Scientific journal of the Fergana State University, 2026)
The article examines the changes in the ecological state of landscapes and methods for their assessment using the example of large cities in the Fergana Valley. Urbanization, industrialization, and increased agricultural activity have a negative impact on natural landscapes and cause environmental problems. Modern geographic information systems (GIS), ecological analysis and modeling, and monitoring methods are used to assess the ecological state of landscapes.